Ah Kee and the glass bottle - Salanitri, Joan, 1944-; Wu, Di. (Maleny, Qld. : Greater Glider Productions, 2001)
"A love story set in old China when merchant caravans travelled the Silk Road. Ah Kee's gift of a blue glass drinking bottle to Li Chong leads her on a perilous journey in storm-ravaged mountains"--Back cover.
For children.
Keywords: Love -- Juvenile fiction; China -- Juvenile fiction